Idiosyncratic risks, bailout, and financial crisis: A copula approach - Wang, Daphne; Nguyen, Khoa Huu (Global Business & Finance Review (GBFR), 2015)
EconStor is a publication server for scholarly economic literature, provided as a non-commercial public service by the ZBW.

Emerging market hedge funds: Analysis of security selection and market timing - Dutta, S. (Banking and Finance Review, 2012)
Recent studies have documented that it is only very recently that the Emerging Market Hedge Funds (EMHFs) have started mimicking the performance pattern of regular Hedge Funds. These findings therefore motivate us to analyze the market timing and security selection skills of EMHF managers. Rolling regression technique is employed to analyze the above mentioned issues on a time-varying dimension. The rolling market timing regression results suggest that the EMHF managers do not exhibit consistently superior security selection or market timing skills even in an up-market scenario. The static market timing models however, indicate significant outperformance due to superior security selection and significant underperformance due to perverse market timing for the EMHFs in general. Multifactor asset class regressions, using fund-level data, reaffirm the notion that the EMHFs mimic the performance pattern reported for mutual funds in the mutual fund literature. © 2012, Banking and Finance Review.
Keywords: Emerging market; Hedge Funds; Security selection; dept.fin; ⛔ No DOI found

Are we overestimating REIT idiosyncratic risk? Analysis of pricing effects and persistence - Abugri, Benjamin A.; Dutta, Sandip (International Review of Economics & Finance, 2014)
This study uses a multifactor REIT-specific model to estimate and compare REIT idiosyncratic volatility vis-A-vis the same from the Fama-French three-factor model. Estimates of conditional idiosyncratic volatility and conditional betas obtained from a multifactor REIT-returns model and a bivariate EGARCH model respectively are found to be positively and significantly related with REIT returns. Consistent with Merton's (1987) predictions, we observe that larger REITs post higher average returns when idiosyncratic risk is introduced in cross-sectional regressions. Persistence of past market-risk does not appear to be short-lived and seems to have a lasting impact on future idiosyncratic volatility. We also observe mild evidence of persistence of past idiosyncratic risk, albeit short-lived, thereby suggesting that past idiosyncratic risk has a short-term impact on future idiosyncratic risk. Published by Elsevier Inc.
Keywords: Conditional betas; Idiosyncratic risk; REITs; dept.fin

Testing trade-off and pecking order models of capital structure: does legal system matter? - Cotei, Carmen; Farhat, Joseph B; Abugri, Benjamin A (Managerial Finance, 2011)
Purpose – This paper aims to examine the link between financing patterns, information asymmetry and legal traditions in 37 countries during the 1990-2004 period. Design/methodology/approach – The analysis is based on three theories: the trade-off theory, pecking order hypothesis and market timing hypothesis. The authors test the predictions of these theories/hypotheses using regression analysis. The econometric method used is panel data with firm and country fixed effects. The authors develop a modified pecking order model which controls for short- and long-term debt level changes and simultaneously test the predictions of all theories. Findings – Consistent with studies for US firms, the results show that firms across all countries adjust toward the target leverage, but with significantly different rate. The long-term debt contribution in the rate of adjustment is 64 percent in common law countries and 51 percent in civil law countries. The ability of the model to explain changes in leverage ratios is higher in common law countries. The authors find support for market timing hypothesis but no support for pecking order of financing. These results support their conjecture that stronger investor protection, higher transparency and well-developed financial markets in common law countries reduce the cost of recapitalization. Research limitations/implications – The limitation of this study comes from lack of data availability to measure contract enforcement, transparency, and corporate governance variables. Future research can incorporate these variables to explain the differences in capital structure decisions across countries with different legal systems. Practical implications – The findings show that firms' capital structure decisions are not only a function of their own characteristics but also the result of legal and financial market development in which they operate. Originality/value – This is the first study that sheds light about rate of adjustment to optimal capital structure and pecking order of financing in 37 countries with different legal traditions and financial market developments. The authors are not aware of any other study that uses a modified pecking order model in an international context. © 2011, © Emerald Group Publishing Limited.
Keywords: Capital; Financial development; International capital structure; Legal systems; Pecking order theory; Trade-off theory; dept.fin; peer-reviewed

Ownership structure, non-interest income and bank risk in ghana - Abugri, Benjamin A; Osah, Theophilus Teye; Andoh, Samuel (Banking and Finance Review, 2016)
This study investigates the relationship between bank ownership structure, non-interest income and risk in an emerging market setting. Our analysis shows that the relationship between product diversification and bank risk is significantly influenced by asset size and ownership structure. In contrast to large banks, small banks are exposed to higher risk when the income share of non-traditional banking activities rise. We also find strong evidence of differences in risk exposure of banks to non-interest income after controlling for ownership structure. Private domestic and private foreign banks experience lower risk with higher non-interest income while the converse is true for public domestic banks. Furthermore, we show that the speed with which risk adjust to non-income activities is faster for domestic private banks than for foreign banks. These results could provide useful information to investors and regulators of banking institutions as they seek to reconcile the important issues of bank ownership structure, income diversification and size on the one hand with the level of risk exposure on the other hand. © 2016, Banking and Finance Review.
Keywords: Bank risk; Ghana; Non-interest income; Ownership structure; dept.eco; dept.fin; ⛔ No DOI found

Are hedge fund returns affected by media coverage of macroeconomic news? - Dutta, Sandip; Thorson, James (Studies in Economics and Finance, 2019)
Purpose: Extant literature suggests that the difficulty associated with the interpretation of macroeconomic news announcements by the market in general in different economic environments, might be the reason why most studies do not find any significant relationship between real-sector macroeconomic variables and financial asset returns. This paper aims to use a different approach to measure macroeconomic news. The objective is to examine if a different measure of a macroeconomic news variable, constructed from media coverage of the same, significantly affects hedge fund returns. Design/methodology/approach: The authors use a news index for unemployment, which is a real-sector variable, constructed from newspaper coverage of unemployment announcements and examine its impact on hedge fund returns. Findings: Contrary to the other studies that examine the impact of macroeconomic news on hedge fund returns, the authors find that media coverage of unemployment news announcements significantly affects hedge fund returns. Practical implications: Overall, this paper demonstrates that the manner in which the market interprets macroeconomic news announcements in different economic environments is probably a more relevant factor for hedge funds and is more likely to impact hedge fund returns. In conjunction with variables – constructed from media coverage of unemployment news announcements – that factor in the manner of interpretation, it is found that surprises also matter for hedge fund returns. This is an important consideration for hedge fund managers as well. Originality/value: To the best of the authors’ knowledge, this is the first study that examines the impact of media coverage of macroeconomic news announcements on hedge fund returns and finds significantly different results with real-sector macro variables. © 2019, Emerald Publishing Limited.
Keywords: Finance; Financial economics; dept.eco; dept.fin; peer-reviewed

Stale economic news, media and the stock market - Birz, Gene (Journal of Economic Psychology, 2017)
I employ a classification of headlines from newspapers and wire services to examine whether stale macroeconomic news affects stock prices. Unlike with individual stocks, the cost of obtaining information about major economic releases is relatively low. Thus, stock prices should adjust to economic news announcements prior to their coverage in newspapers. I find statistically and economically significant relationship between stale news stories on unemployment and next week's S&P 500 returns. This effect is then completely reversed during the following week. These findings show that investors are affected by salient information and support the hypothesis that investors overreact to stale macroeconomic news reported in newspapers. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Attention; Efficient markets; Macroeconomic announcements; Media; Salience; dept.eco; dept.fin

Dynamic responses and tail-dependence among commodities, the US real interest rate and the dollar - Huang, Wanling; Mollick, André Varella; Nguyen, Khoa Huu (Empirical Economics, 2017)
Keywords: dept.fin

Examining the dynamic linkages of performance and volatility of REIT returns - Dania, Akash; Dutta, Sandip (The Journal of Wealth Management, 2017)
This article extends the literature on the financial performance of real estate investment trusts (REITs) by examining whether U.S. REIT returns are impacted by global REITs and other real estate subsectors, such as the U.S. Real Estate Index (USRE) and the U.S. Mortgage Finance Index (USMF). The authors also explore the issue of volatility transmission and the asymmetric effect of volatility spillover on U.S. REIT returns from innovations originating in other real estate subsectors and Global REITs. Results suggest that U.S. REITs are impacted by USRE and USMF returns. There is also evidence of volatility spillover from key real estate constituents-that is, USRE and USFM returns and global REIT markets. These results can be attributed to the changing dynamics of the real estate sector and the gradual integration of the global real estate sector as an asset class. These findings have strong implications for constructing global portfolios including REITs.
Keywords: dept.eco; dept.fin

Institutional ownership and the spillover effects of shareholder activism - Jory, Surendranath; Ngo, Thanh; Nguyen, Khoa Huu (International Journal of Corporate Governance, 2017)
Keywords: dept.fin